Penyelesaian Sengketa Konsumen melalui Badan Penyelesaian Sengketa Konsumen - Annisa Gita Prassiwi; I Gusti Ngurah Adnyana; Dewi Ayu Rahayu; Dhaniar Eka Budiastanti (University of Merdeka Malang, 2023)
Currently there are many problems in consumer protection. The increasing number of goods and/or service transactions, the increasing number of consumer disputes in Indonesia. Based on data from the Malang City Consumer Dispute Settlement Agency, there were several problems reported to the Consumer Dispute Settlement Agency, including problems with property, Regional Drinking Water Companies and leasing. The type of research used is normative juridical, namely studying and analyzing cases that have occurred using Law no. 8 of 1999 concerning Consumer Protection. The aims of this research is expected to improve the performance of the Consumer Dispute Settlement Agency so that when there is a problem in society related to consumer disputes it can be resolved properly. Besides that, it can add knowledge, especially to business actors so that every transaction must be more careful and consumers when making a transaction must pay more attention to the information available so that there are no errors in the end. The results of this study include the dispute resolution mechanism by the Consumer Dispute Settlement Agency which is carried out through five stages as well as consumer dispute resolution efforts.